Blockchain Utilization in Secure and Decentralized Web 3.0 Application Development - Jaenudin, Jejen; Zahran, Aziz; Mahdiana, Deni (Politeknik Ganesha Medan, 2024)
The implementation of blockchain technology in the creation of secure and decentralized Web 3.0 applications has grown in significance. Blockchain, an industry-spanning distributed ledger technology, has facilitated substantial advancements in information and communication technology, among others. Regarding Web 3.0, this study examines how the implementation of blockchain technology can enhance decentralization and security. By conducting a literature review, this study examines how the implementation of blockchain technology in the development of Web 3.0 applications significantly improves data security. Through the implementation of robust cryptographic features and distributed security principles, the outcomes demonstrate that blockchain can effectively safeguard data while it is being transmitted and stored via Web 3.0 applications. This is a crucial step in the direction of resolving the security issues that are frequently encountered in the digital environment of today. Furthermore, blockchain technology facilitates enhanced decentralization within Web 3.0 applications. Blockchain applications reduce their reliance on a central authority, thereby enhancing their resilience against single-system malfunctions and monopoly control. Furthermore, it facilitates the development of platforms that are more equitable and transparent, granting users greater authority over their data and interactions.